LEGAL POSITION OF THE INDONESIAN NOTARY PUBLIC ASSOCIATION AS A LEGAL ENTITY AFTER THE EFFECTIVENESS OF ARTICLE 82 OF THE UUJN JO. PERMENKUMHAM NO. 24 OF 2025 - Bimo Pangestu; Herlin Hera Fransasti (RADJA PUBLIKA, 2026)
This study aims to determine and analyze the legal status of the Indonesian Notary Association (INI) as a Notary Professional Organization after the enactment of Article 82 of the Notary Law (UUJN) in conjunction with the Minister of Law and Human Rights Regulation Number 24 of 2025, which has caused polemics among legal experts regarding INI before and after the enactment of these regulations. This study is based on the situation of changes in the substantive legislation of the Notary Organization and will have implications for the enforcement of the code of ethics regarding changes and shifts in the legal status of INI as an organization. This study uses a normative legal research method in the form of a statute approach, and legal explanations (doctrine), as well as scientific information or literature and descriptive qualitative analysis of the law, especially primary, secondary, and tertiary laws, to determine the boundaries and potential of existing organizations, as well as normative legal consequences. The results of this study indicate that legally INI is a Legal Entity Association recognized as an association or association, namely as Staatsblad 1870 Number 64. Although the state will provide legitimacy and certain functions of authority are not attributable to public power, this shows that INI has not changed its status to a State Organ. However, the development of these regulations has caused INI's position to become a combination because it has a coaching and supervisory role related to state authority through the Notary Supervisory Board. This study concludes that INI remains an organization that does not receive public accountability, so there is a need for strengthening the limits of authority and harmonization between notary organizations and the government to avoid overlapping supervision and ensure legal certainty in the implementation of notary positions.